2015
DOI: 10.1007/s13197-015-2027-5
|View full text |Cite
|
Sign up to set email alerts
|

Edible antimicrobial films based on microencapsulated lemongrass oil

Abstract: Edible films and coatings have been proposed as viable alternatives for the preservation of fresh food such as fruit, meat, fish and cheese. They can be designed to contain natural antioxidants, vitamins and antimicrobials in order to extend shelf life of the product keeping the natural sensorial properties. Essential oils have been targeted as potential active principles for edible films and coatings given their wellrecognized antioxidant, antimicrobial and sensory properties. In the present work, lemongrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…The macrodilution assay is performed in tubes containing a minimum volume of 2 mL, while the microdilution method utilizes smaller volumes of tested antimicrobial substances and is performed using microtitration plates (OIE ). In several studies assessing the antimicrobial activity of coating formulations and films by broth dilution tests, the most widely used methods for end point determination include the optical density measurements (Min and others ; Moreira and others ; Bustos and others ), the enumeration of viable cells (He and others ; Guo and others ), and the absorbance evaluation (Severino and others ).…”
Section: Methods For the Antimicrobial Evaluation Of Edible Films Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The macrodilution assay is performed in tubes containing a minimum volume of 2 mL, while the microdilution method utilizes smaller volumes of tested antimicrobial substances and is performed using microtitration plates (OIE ). In several studies assessing the antimicrobial activity of coating formulations and films by broth dilution tests, the most widely used methods for end point determination include the optical density measurements (Min and others ; Moreira and others ; Bustos and others ), the enumeration of viable cells (He and others ; Guo and others ), and the absorbance evaluation (Severino and others ).…”
Section: Methods For the Antimicrobial Evaluation Of Edible Films Andmentioning
confidence: 99%
“…Depending on application, antimicrobial coatings are formulated to provide either a quick release or a slow release of the antimicrobial over storage time. Many recent studies have been published on the evaluation of both the antimicrobial properties of edible films and coatings and the release mechanism of the incorporated antimicrobial agents (Boyaci and others ; Bustos and others ; Chen and Liu ).…”
Section: Methods For the Antimicrobial Evaluation Of Edible Films Andmentioning
confidence: 99%
“…Correlations between films with microcapsules of lemongrass essential oil and this oil without microcapsules in films of alginate matrix. Peppas model, showed values of the η exponent in both cases was in the zone indicative of a Fickian release mechanism: n = 0.205 < 0.43 for microcapsule spheres and n = 0.311 < 0.5 for thin films [157] Cooper cations…”
Section: Release Of the Active Substances In Edible Coatingsmentioning
confidence: 95%
“…During recent years, the interest in the bio-efficacy of essential oils and their uses as natural antimicrobials in environmentally friendly products has rapidly increased. Several authors have reported on innovations in smart packaging food systems based on essential oils [35][36][37][38][39][40][41]. Among essential oils, the oil obtained from lemongrass plants of genus Cymbopogon, particularly of C. citratus (CAS RN 8000-29-1) known as citronella or lemongrass oil, has been studied and used due to its broad-spectrum antimicrobial activity, pleasant aroma and uses in food, pharmaceutical and cosmetic products, as well as in mosquito repellents and natural pesticides.…”
Section: Microencapsulated Antimicrobial Essential Oilsmentioning
confidence: 99%
“…None of them reported on the antimicrobial evaluation of citronella oil, encapsulated in impermeable yet pressure-sensitive microcapsules that require a mechanical activation to release the active ingredient. [38] emulsification-separation method, sodium caseinate wall average 22 µm edible antimicrobial films for food products Khounvilay et al [61] spray drying, carboxymethylated tamarind gum walls 3.8-6.3 µm not specified Table 2. Cont.…”
Section: Microencapsulated Antimicrobial Essential Oilsmentioning
confidence: 99%